Molecular epidemiology of hepatitis B virus in Córdoba, Argentina - Gallego, Fernando (2014)
The analysis of the genomes of hepatitis B virus (HBV) identifies phylogenetic variants calledgenotypes, which may lead to distinct biological and clinical behaviors.Objectives: The aim of this study was to describe the current molecular epidemiology and genetic diversityof HBV in Córdoba, Argentina. Study design: A total of 52 HBV samples, 40 from HBV mono-infected and 12 from human immuno-deficiency virus (HIV)-HBV co-infected patients, were sequenced in the S gene and in the basal corepromoter-precore (BCP-pC) region.Results: Presence of subgenotypes F1b (35%) and F4 (17.5%), subgenotype A2 (37.5%), C (5.0%) (subgeno-type could not be defined) and D (5.0%) (subgenotype D2, and the other could not be defined) wereobserved among mono-infected patients. The co-infected individuals displayed a different genotypedistribution: sub-genotype A2 was the most common (75.0%), followed by subgenotype F1b (25.0%).Conclusions: These results showed two epidemiologic scenarios: the mono-infected population may rep-resent the ethnic composition of the current human population of Córdoba, where the Amerindian(genotype F) and European origins (subgenotype A2) account for the 90% of the samples; for the co-infected patients, the high prevalence of subgenotype A2 resemble previous analyses from Buenos Aires.In addition, mutations in hepatitis B surface antigen (HBsAg), polymerase and BCP-pC regions wereidentified, mainly in chronic or co-infected patients.